2012
DOI: 10.1103/physrevlett.108.137203
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field Control of Nonvolatile Magnetization inCo40Fe40B20/Pb(Mg1/3

Abstract: We report a large and nonvolatile bipolar-electric-field-controlled magnetization at room temperature in a Co(40)Fe(40)B(20)/Pb(Mg(1/3)Nb(2/3))(0.7)Ti(0.3)O(3) structure, which exhibits an electric-field-controlled looplike magnetization. Investigations on the ferroelectric domains and crystal structures with in situ electric fields reveal that the effect is related to the combined action of 109° ferroelastic domain switching and the absence of magnetocrystalline anisotropy in Co(40)Fe(40)B(20). This work prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
167
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(185 citation statements)
references
References 32 publications
15
167
1
2
Order By: Relevance
“…However, this does not meet present development of information storage which requests nonvolatility. 34 Recently, Zhang et al 21 have demonstrated a nonvolatile electrical manipulation of magnetism in CoFeB/(001) PMN-PT ( Fig. 2(a)) that differs from the previous work.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…However, this does not meet present development of information storage which requests nonvolatility. 34 Recently, Zhang et al 21 have demonstrated a nonvolatile electrical manipulation of magnetism in CoFeB/(001) PMN-PT ( Fig. 2(a)) that differs from the previous work.…”
contrasting
confidence: 41%
“…The piezoresponse force microscopy (PFM) measurements were also performed to investigate the FE domain structures, revealing the existence of these domain switchings. 21 It should be mentioned that the in-plane lattice parameters of r1/r3 and r2/r4 are different along the [110] direction so that different domain switching will induce various interesting strain states as illustrated in Fig. 3 To obtain the value of the net 109 • switching in this special type of PMN-PT (100) substrate, reciprocal space mapping (RSM) was carried out to study the distribution of FE domains under various electric fields due to their different lattice parameters (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, how do we understand the influence of the FE domain (ferroelastic) switching on both the static magnetic domain (wall) morphology and its dynamic evolution process? Recent works have reported such mutual magnetic-FE domain coupling in FE crystal-based multiferroic heterostructures, such as CoFe/(001)BTO [67,68,96], CoFeB/(001)PMN-PT [97], and more recently in CoFe 2 O 4 (or NiFe 2 O 4 )/(100)BTO [69], but the results in multiferroic magnetic/FE composite thin films are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Multiferroic heterostructures, simultaneously exhibiting ferromagnetism, ferroelectricity and ferroelasticity, have attracted great interest due to the strong strainmediated magnetoelectric (ME) coupling and shown promising applications for tunable magnetic devices. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] More interestingly, in these structures, a single control parameter of voltage is used to induce a lattice strain through the converse piezoelectric effect in the ferroelectric phase, which in turn tailors the magnetic properties in the mechanically coupled magnetic phase through the magnetoelastic effect. 25,[30][31][32][33][34][35][36][37][38][39][40][41] Thus, devices made of such heterostructures are ultrafast, compact, quiet, energy efficient and susceptible to be integrated into electronic circuits.…”
Section: Introductionmentioning
confidence: 99%